Respon Pertumbuhan dan Hasil Tanaman Bunga Kol Akibat Pemberian dan Konsentrasi PGPR - Aprilia Hartanti; Ida Sugeng Suyani; Nanang Wahyudi (Universitas Islam Raden Rahmat, Malang, 2023)
This research is expected to determine the effect of concentration and administration of PGPR (Plant Growth Promoting Rhizobacteria) on the growth and yield of cauliflower (Brassica Oleraceae var. Botrytis L). The research results obtained are: 1). PGPR concentration did not affect the growth and yield of cauliflower, 2). The treatment with PGPR had a significant effect on the results of analysis of variance on growth and yield of cauliflower, 3). There was no interaction between the administration of PGPR at a certain concentration and the time of administration on the growth and yield of cauliflower plants. The research method used was a 2-factorial Randomized Block Design (RBD), namely the first factor was the concentration of PGPR given with 4 levels of treatment and the second factor when giving PGPR with 3 levels of treatment, resulting in 12 experimental combinations with 3 repetitions so that there were 36 experimental plots . Data will be analyzed using 5% BNT test for single factors and 5% Duncan's distance test (DMRT) for interaction factors.